Porous aluminum magnesium-calcium material and preparation method thereof

By preparing porous aluminum magnesium-calcium materials, using the combination of aluminum sol and lightly calcium dolomite powder and magnesium powder, the problem of degradation of traditional magnesium-calcium refractory materials at high temperatures is solved, and the high density and good sintering performance of the materials are achieved.

CN119551995APending Publication Date: 2025-03-04SHANXI LUWEIBAO TAIGANG REFRACTORIES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411774554.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04

Smart Images

  • Figure CN119551995A_ABST
    Figure CN119551995A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of refractory materials, and particularly relates to a porous aluminum-made magnesium-calcium material which comprises, by mass, 50% of light-burned dolomite powder, 47-49% of light-burned magnesium powder and 1-3% of alumina sol, and the sum of the content of all the components is 100%. According to the invention, Al2O3 and CaO are combined to form a porous structure, closed pores are rounded, pore size distribution is relatively uniform, the melting point of a calcium-aluminum compound Ca3Al2O6 generated by combining Al2O3 and CaO is relatively low relative to the sintering temperature, so that sintering is further promoted, and the generated calcium-aluminum compound can form a layer of coating film on the surface of the magnesia-calcium sand, so that the magnesia-calcium sand can be effectively prevented from being in contact with water in air, and the service life of the magnesia-calcium sand is prolonged. Therefore, the hydration of the magnesia-calcium sand is prevented, and the hydration resistance of the magnesia-calcium sand is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and specifically relates to a porous aluminum-made magnesium-calcium material and a preparation method thereof. Background Art

[0002] Magnesium-calcium refractory is a commonly used alkaline refractory, mainly composed of periclase (MgO) and calcium (CaO). Magnesium-calcium refractory has the advantages of high refractoriness, good kiln skin resistance, stable thermal shock resistance and purification of molten steel. It is often used as lining materials for refining furnaces and cement rotary kiln firing zones. In addition, my country has abundant resources of magnesite and dolomite at low prices, which has led to the rapid development of magnesium-calcium refractory.

[0003] At present, the performance of traditional magnesium-calcium refractory materials is reduced during the preparation process due to strong slag erosion and wear and thermal shock caused by sudden temperature changes. Although the use of aluminum sol as a binder can reduce or even reduce the impurity components caused by the binder, the molding performance of the aluminum sol binder material is very poor. The aluminum sol with an added concentration exceeding 4% (weight percentage) will have problems such as excessive water and poor mechanical properties, which will have great limitations. Summary of the invention

[0004] The purpose of the present invention is to provide a porous aluminum magnesium-calcium material and a preparation method thereof, aiming to solve the problem that the traditional magnesium-calcium refractory materials are subjected to strong slag erosion and wear and thermal shock caused by sudden temperature change during the preparation process, thereby reducing their performance. Although aluminum sol is used as a binder, the impurity components caused by the binder can be developed in the direction of less or even zero impurities. However, since the molding performance of the aluminum sol binder material is very poor, the aluminum sol with an added concentration exceeding 4% (weight percentage) will have the problems of excessive water and poor mechanical properties, which will have great limitations.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a method for preparing a porous aluminum-based magnesium-calcium material, comprising the following components and mass fractions: 50% light-burned dolomite powder, 47-49% light-burned magnesium powder and 1-3% aluminum sol, and the sum of the contents of each component is 100%.

[0006] A method for preparing a porous aluminum magnesium-calcium material comprises the following steps:

[0007] S1, placing dolomite powder in a crucible, and then placing it in a muffle furnace, calcining the dolomite powder at high temperature to obtain a light-burned dolomite powder raw material;

[0008] S2, using a vibrating screening machine to screen the light-burned magnesium powder raw material, and storing the screened light-burned magnesium powder raw material;

[0009] S3, weighing and selecting the raw materials according to percentage, wherein 50% of light-burned dolomite powder, 47-49% of light-burned magnesium powder are raw materials and 1-3% of aluminum sol is an additive;

[0010] S4, put the prepared raw materials in S3 and an appropriate amount of alcohol into a ball mill, and then use a ball mill to mix them. Al2O3 particles will achieve a good coating effect because of their high dispersibility;

[0011] S5, placing the powder mixed evenly in S4 in a drying oven for drying;

[0012] S6, after the powder in S5 is cooled, take it out, then grind the powder into fine powder with an agate mortar, add anhydrous resin as a binder to the ground fine powder, and then mix them evenly;

[0013] S7, using a manual tablet press to press the raw materials mixed in S6 into a cylindrical sample;

[0014] S8, placing the cylindrical sample in S7 in a drying oven for secondary drying;

[0015] S9. Place the cylindrical sample dried in S8 in a muffle furnace and calcine it at high temperature to obtain a finished product.

[0016] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the calcination temperature of the muffle furnace in S1 is controlled at 850° C. and kept warm for 3 hours.

[0017] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the screen of the vibrating screening machine in S2 is selected to be less than 200 meshes.

[0018] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the CaO content of the raw material in S3 is fixed at 30%.

[0019] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the mixing time of the raw materials in the ball mill in S4 is set to 6 hours.

[0020] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the drying time of the drying box in S5 and S8 is 12 hours.

[0021] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the mass fraction of the anhydrous resin in S6 is 4% of the total mass fraction of the raw materials.

[0022] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the diameter of the cylindrical sample pressed into by the raw material in S7 is 30 mm.

[0023] As a preferred method for preparing a porous aluminum magnesium-calcium material of the present invention, the temperature of the muffle furnace in S9 is controlled to be calcined at 1650° C. and kept warm for 2 hours.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] By adding aluminum sol, the volume density of magnesium-calcium samples can be effectively increased. Since the particle size of the added aluminum sol is nanometer-level, it can promote solid-phase sintering of the material. The added Al2O3 reacts with CaO to generate low-melting-point mineral Ca3Al2O6, accompanied by a certain volume expansion, which increases the density of the material and reduces the apparent porosity. After the nano-aluminum sol is introduced into the magnesium-calcium refractory material, the Al2O3 generated by the pyrolysis of the aluminum sol forms a porous structure in the form of physical bonding, and the pores are mostly rounded closed pores. On the other hand, Al2O3 reacts with CaO to generate a low-melting-point phase Ca3Al2O6, which promotes sintering. The addition of aluminum sol can effectively improve the sintering performance and hydration resistance of magnesium-calcium refractory materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0027] Figure 1 It is a schematic diagram of the preparation process of the present invention;

[0028] Figure 2 It is a schematic diagram of the phase composition of the samples of the present invention to which different contents of aluminum sol are added;

[0029] Figure 3 It is a schematic diagram of the microstructure of the fracture of aluminum sol samples with different contents in the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] See also Figure 1-3 The present invention provides the following technical solution: a porous aluminum magnesium-calcium material, comprising the following components and mass fractions: 50% light-burned dolomite powder, 47-49% light-burned magnesium powder and 1-3% aluminum sol, and the sum of the contents of each component is 100%.

[0032] A method for preparing a porous aluminum magnesium-calcium material comprises the following steps:

[0033] S1, placing dolomite powder in a crucible, and then placing it in a muffle furnace, calcining the dolomite powder at high temperature to obtain a light-burned dolomite powder raw material;

[0034] S2, using a vibrating screening machine to screen the light-burned magnesium powder raw material, and storing the screened light-burned magnesium powder raw material;

[0035] S3, weighing and selecting the raw materials according to percentage, wherein 50% of light-burned dolomite powder, 47-49% of light-burned magnesium powder are raw materials and 1-3% of aluminum sol is an additive;

[0036] S4, put the prepared raw materials in S3 and an appropriate amount of alcohol into a ball mill, and then use a ball mill to mix them. Al2O3 particles will achieve a good coating effect because of their high dispersibility;

[0037] S5, placing the powder mixed evenly in S4 in a drying oven for drying;

[0038] S6, after the powder in S5 is cooled, take it out, then grind the powder into fine powder with an agate mortar, add anhydrous resin as a binder to the ground fine powder, and then mix them evenly;

[0039] S7, using a manual tablet press to press the raw materials mixed in S6 into a cylindrical sample;

[0040] S8, placing the cylindrical sample in S7 in a drying oven for secondary drying;

[0041] S9, placing the cylindrical sample dried in S8 in a muffle furnace, and calcining it at high temperature to obtain a finished product;

[0042] Specifically, by adding aluminum sol, the volume density of the magnesium-calcium sample can be effectively increased. Since the particle size of the added aluminum sol is nanometer-scale, it can promote solid-phase sintering of the material. The added Al2O3 reacts with CaO to generate a low-melting-point mineral Ca3Al2O6, accompanied by a certain volume expansion, which increases the density of the material and reduces the apparent porosity. After the nano-aluminum sol is introduced into the magnesium-calcium refractory material, the Al2O3 generated by the pyrolysis of the aluminum sol forms a porous structure in the form of physical bonding, and the pores are mostly rounded closed pores. On the other hand, Al2O3 reacts with CaO to generate a low-melting-point phase Ca3Al2O6, which promotes sintering. The addition of aluminum sol can effectively improve the sintering performance and hydration resistance of the magnesium-calcium refractory material.

[0043] Preferably, the calcination temperature of the muffle furnace in S1 is controlled at 850° C. and kept at this temperature for 3 hours.

[0044] Preferably, the screen of the vibrating screening machine in S2 is selected to be below 200 meshes.

[0045] Preferably, the CaO content of the raw material in S3 is fixed at 30%.

[0046] Preferably, the mixing time of the raw materials in the ball mill in S4 is set to 6 hours.

[0047] Preferably, the drying time of the drying box in S5 and S8 is 12 hours.

[0048] Preferably, the mass fraction of the anhydrous resin in S6 is 4% of the total mass fraction of the raw materials.

[0049] Preferably, the diameter of the cylindrical sample pressed from the raw material in S7 is 30 mm.

[0050] Preferably, the temperature of the muffle furnace in S9 is controlled at 1650° C. for calcination and kept at this temperature for 2 hours.

[0051] Working principle: First, put the dolomite powder in a crucible, and then put it in a muffle furnace, calcine the dolomite powder at high temperature to obtain light-burned dolomite powder raw material, use a vibrating screener to screen the light-burned magnesium powder raw material, and store the screened light-burned magnesium powder raw material, and then weigh the raw materials according to percentage, among which 50% of light-burned dolomite powder, 47-49% of light-burned magnesium powder are raw materials and 1-3% of aluminum sol is additive. Put the prepared raw materials and appropriate amount of alcohol into a ball mill, and then use a ball mill to mix them. Al2O3 particles will achieve a good coating effect because of their high dispersibility. Place the evenly mixed powder in a drying box for drying, take it out after the powder cools down, and then use agate to coat the powder. The mortar is ground into fine powder, and anhydrous resin is added to the ground fine powder as a binder, and then the mixture is evenly mixed. Then, the mixed raw materials are pressed into cylindrical samples using a manual tablet press, and the cylindrical samples are placed in a drying box for secondary drying. Finally, the dried cylindrical samples are placed in a muffle furnace and calcined at high temperature to obtain the finished product. By adding aluminum sol, the volume density of the magnesium-calcium sample can be effectively increased. Since the particle size of the added aluminum sol is nanometer-level, the material is solid-phase sintered due to the small nanoparticle size, large specific surface area and high chemical activity. The added Al2O3 reacts with CaO to generate low-melting-point mineral Ca3Al2O6, accompanied by a certain volume expansion, which increases the density of the material and reduces the apparent porosity. After the nano aluminum sol is introduced into the magnesium-calcium refractory material, the Al2O3 generated by the pyrolysis of the aluminum sol forms a porous structure in the form of physical bonding, and the pores are mostly rounded closed pores. On the other hand, Al2O3 reacts with CaO to generate the low melting point phase Ca3Al2O6, which promotes sintering. The addition of aluminum sol can effectively improve the sintering performance and hydration resistance of magnesium-calcium refractory materials.

[0052] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous aluminum magnesium calcium material, characterized in that: The invention comprises the following components and mass fractions: 50% of light-burned dolomite powder, 47-49% of light-burned magnesium powder and 1-3% of aluminum sol, and the sum of the contents of the components is 100%.

2. A method for preparing a porous aluminum magnesium-calcium material, characterized in that: The following steps are involved: S1, placing dolomite powder in a crucible, and then placing it in a muffle furnace, calcining the dolomite powder at high temperature to obtain a light-burned dolomite powder raw material; S2, using a vibrating screening machine to screen the light-burned magnesium powder raw material, and storing the screened light-burned magnesium powder raw material; S3, weighing and selecting the raw materials according to percentage, wherein 50% of light-burned dolomite powder, 47-49% of light-burned magnesium powder are raw materials and 1-3% of aluminum sol is an additive; S4, put the prepared raw materials in S3 and an appropriate amount of alcohol into a ball mill, and then use a ball mill to mix them. Al2O3 particles will achieve a good coating effect because of their high dispersibility; S5, placing the powder mixed evenly in S4 in a drying oven for drying; S6, after the powder in S5 is cooled, take it out, then grind the powder into fine powder with an agate mortar, add anhydrous resin as a binder to the ground fine powder, and then mix them evenly; S7, using a manual tablet press to press the raw materials mixed in S6 into a cylindrical sample; S8, placing the cylindrical sample in S7 in a drying oven for secondary drying; S9. Place the cylindrical sample dried in S8 in a muffle furnace and calcine it at high temperature to obtain a finished product.

3. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The calcination temperature of the muffle furnace in S1 is controlled at 850° C. and maintained at this temperature for 3 hours.

4. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The screen of the vibrating screening machine in S2 is selected to be below 200 meshes.

5. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The CaO content of the raw material in S3 is fixed at 30%.

6. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The mixing time of the raw materials in the ball mill in S4 is set to 6 hours.

7. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The drying time of the drying box in S5 and S8 is 12 hours.

8. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The mass fraction of the anhydrous resin in the S6 is 4% of the total mass fraction of the raw materials.

9. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The diameter of the cylindrical sample pressed from the raw material in S7 is 30 mm.

10. The method for preparing a porous aluminum magnesium-calcium material according to claim 2, characterized in that: The temperature of the muffle furnace in S9 is controlled at 1650° C. for calcination and maintained for 2 hours.